Connecting the Dots: Systems Practice & Political Economy Analysis - Walker, Tjip; Jacobstein, David (2017)
This slide deck, from a presentation to the Local Systems Community by Tjip Walker and David Jacobstein, shows various ways in which assessing the political economy of a context and understanding that context through the lens of systems thinking can reinforce each other. Effective systems practice should be grounded in the incentives and power dynamics of a particular local system; thinking and working politically requires understanding the systems dynamics of an issue or sector.

Using elements of DCED Standards for CLA - Mitra, Bilash; Jalil, Mohammad Muaz (2018)
Introduction used in the DCED-BEAM seminar in Nairobi

Thinking and working politically: An introduction to key ideas, examples and further reading - Laws, Ed; Marquette, Heather (2018)

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (2016)

The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen Barder explores the implications of complexity theory for development policy. He explains how traditional economic models have tried and failed to understand why some countries have managed to improve living standards while other countries have not.
Keywords: IMPORTANT

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

Complexity & Development 2.0: From Agreeing We Should Adapt to Creating the Conditions that Enable Adaptation - Ang, Yuen Yuen (2018)
The field of global development has reached a critical turning point. Almost gone is the mechanical, one-size-fits-all “good governance” paradigm of the past. In its place is a growing embrace of complexity and systems thinking. While this is an encouraging shift in the right direction, the discussion mostly ends by concluding that we should adapt. Yuen Yuen Ang urges that it’s time to take our conversation on “complexity & development” to the next level: how to enable adaptation. Effective adaptation doesn’t automatically arise just because we desire it—rather, it requires certain enabling conditions. In How China Escaped the Poverty Trap (2016), she introduces a generic complexity 2.0 framework that she terms “directed improvisation.” Effective adaptation, Yuen Yuen argues, requires a paradoxical blend of top-down direction and bottom-up improvisation. Such a system can be created—and produce dramatic results and adaptive solutions—even within a closed political regime like China.